1999
DOI: 10.1165/ajrcmb.20.5.3260
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Alveolar Macrophage Gelatinase B (MMP-9) in Patients with Idiopathic Pulmonary Fibrosis

Abstract: Alveolar macrophages (AM) express gelatinase B, a member of the matrix metalloproteinase family involved in the degradation and remodeling of extracellular matrix components. We evaluated the expression of gelatinase B in the course of idiopathic pulmonary fibrosis (IPF) by studying alveolar macrophages in culture AM and bronchoalveolar lavage fluid from 12 untreated patients with IPF, 11 patients with IPF under treatment with steroid and immunosuppressive agents, and 10 control subjects. By using zymography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 39 publications
4
82
0
2
Order By: Relevance
“…It has been suggested that the tissue phenotype of fibrosis (primarily the exaggerated extracellular matrix deposition) results from dysregulation of the synthesis and degradation of extracellular matrix proteins-a process that could involve several members of the MMP family. Thus, MMP-1 (collagenase-1 that degrades fibrillar collagens) as well as MMP-2 and MMP-9 (gelatinases A and B, which have a broad range of substrates including type IV collagens from basement membranes) have previously been reported to be up-regulated in human pulmonary fibrosis and animal models of pulmonary fibrosis (17)(18)(19). In our data set, MMP-1, MMP-2, and MMP-9 were significantly higher in UIP lungs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the tissue phenotype of fibrosis (primarily the exaggerated extracellular matrix deposition) results from dysregulation of the synthesis and degradation of extracellular matrix proteins-a process that could involve several members of the MMP family. Thus, MMP-1 (collagenase-1 that degrades fibrillar collagens) as well as MMP-2 and MMP-9 (gelatinases A and B, which have a broad range of substrates including type IV collagens from basement membranes) have previously been reported to be up-regulated in human pulmonary fibrosis and animal models of pulmonary fibrosis (17)(18)(19). In our data set, MMP-1, MMP-2, and MMP-9 were significantly higher in UIP lungs.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP-1 expression is correlated with stages of disease progression and may prevent MMPinduced extracellular matrix degradation, and, as a consequence, may participate in the accumulation of extracellular matrix. MMP detection could be proposed as a prognosis factor in lung fibrosis as described for MMP-9 (Lemjabbar et al, 1999).…”
Section: Lung Fibrosismentioning
confidence: 99%
“…MMP-2 is localized in structural cells like regenerated alveolar epithelial, bronchial epithelial cells and fibroblasts. In lung fibrosis, MMP-2 could play a role in the regeneration of alveolar epithelial cells Lemjabbar et al, 1999;Manoury et al, 2005;Scabilloni et al, 2005). The expression of the two gelatinases (MMP-2 and MMP-9) at different stages of fibrosis suggests that MMP-9 could be rather linked to inflammation-induced tissue remodeling, while MMP-2 may be associated with an impaired tissue remodeling leading to pathological collagen deposition and interstitial fibrosis.…”
mentioning
confidence: 99%
“…A previous study revealed that latent gelatinase B, as well an active form, was significantly increased in culture medium (24 hrs) of activated alveolar macrophages from bronchoalveolar lavage of patients with idiopathic pulmonary fibrosis 30. Thus, it is reasonable to hypothesize that surfactant induced a macrophage‐mediated gelatinolytic activity in our coculture model with myofibroblasts since the addition of surfactant caused disruption of the integrity of the myofibroblast monolayer.…”
Section: Discussionmentioning
confidence: 76%